Implementasi Sistem Akuntansi Syariah Dalam Pengelolaan Asuransi Syariah Di Indonesia - Gunawan Aji; Rhetha, Syintia Amanda; Eka Kurniawati; Lia Olivia Zahara (STIKes Ibnu Sina Ajibarang, 2024)
Sharia insurance as a financial institution is required to prepare financial reports in accordance with PSAK 108. The use of accounting by a company is very important in the current situation, especially sharia insurance which seeks to increase client trust. However, rapid expansion without other supporting factors, including employees who are experts in sharia, has resulted in a lack of sharia-related knowledge among customers. This research uses the literature study method to conduct qualitative descriptive research. The aim is to better understand how Indonesian sharia insurance implements a sharia accounting system to ensure sharia insurance business activities comply with sharia principles and fulfill the public's desire for compliant financial solutions. The findings show that the implementation of this sharia accounting system ensures that sharia insurance business activities comply with sharia principles and fulfill the public's desire for financially sound financial solutions